2018
DOI: 10.3390/s18093125
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Rayleigh-Based Distributed Optical Fiber Sensors Bonded to Reinforcing Bars in Bending

Abstract: Distributed Optical Fiber Sensors (DOFSs), thanks to their multiple sensing points, are ideal tools for the detection of deformations and cracking in reinforced concrete (RC) structures, crucial as a means to ensure the safety of infrastructures. Yet, beyond a certain point of most DOFS-monitored experimental tests, researchers have come across unrealistic readings of strain which prevent the extraction of further reliable data. The present paper outlines the results obtained through an experimental test aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 21 publications
(32 reference statements)
3
42
0
1
Order By: Relevance
“…The spikes that are observed in the strain curves at larger loads are not real, likely due to the correlation algorithm used to track the Rayleigh shift in the OFDR interrogator, which can fail when a very large spatial strain gradient occurs. Interestingly, similar spikes have been observed in other applications [36], yet were ascribed to physically-induced anomalies rather than to a limitation of the measurement technique. Unfortunately, due to the squeezing effect, the strain gradient reaches high values early on during the test, although the strain in the middle of the bar is still within the measurable range.…”
Section: Resultssupporting
confidence: 77%
“…The spikes that are observed in the strain curves at larger loads are not real, likely due to the correlation algorithm used to track the Rayleigh shift in the OFDR interrogator, which can fail when a very large spatial strain gradient occurs. Interestingly, similar spikes have been observed in other applications [36], yet were ascribed to physically-induced anomalies rather than to a limitation of the measurement technique. Unfortunately, due to the squeezing effect, the strain gradient reaches high values early on during the test, although the strain in the middle of the bar is still within the measurable range.…”
Section: Resultssupporting
confidence: 77%
“…As a result, the suitability of optical fiber systems in SHM has already been tested for various experiments in the laboratory, see e.g. (Bado, Casas, & Barrias, 2018;Bao, Meng, Chen, Chen, & Khayat, 2015;Sienko, Bednarski, & Howiacki, 2019;Zeng et al, 2002), as well as field applications, see e.g. (Barrias, Rodriguez, Casas, & Villalba, 2018;Brault, Hoult, Greenough, & Trudeau, 2019;Gli si c, Posenato, & Inaudi, 2007;Matta, Bastianini, Galati, Casadei, & Nanni, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In most cases the DOFS are attached directly to the surface of the reinforcement-bars (rebars) before the latter are embedded inside concrete. Multiple studies [ 4 , 8 , 9 , 10 , 11 ] have demonstrated that the technique with which this bonding is achieved has a prominent role in the quality of the extracted data. Indeed, the highly sensitive nature of these hair-like fibers intrinsically exacerbates the probability of its malfunctioning and/or rupture during the concrete casting, maneuvering and testing phase.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of this issue has only lately been recognized as all the produced publications date back to last decade [ 12 , 13 , 14 , 15 ]. Worthy of mention, are two extensive studies analyzing the influence of different bonding adhesives on the strain output of polyamide cladded DOFS attached to bare rebars [ 11 ] and concrete surfaces [ 16 ]. Yet, no definitive comparative study has been developed for the case of DOFS bonded to rebars when embedded inside RC structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation